2018
DOI: 10.1111/age.12718
|View full text |Cite
|
Sign up to set email alerts
|

Gene set enrichment analysis of SNP data in dairy and beef cattle with bovine respiratory disease

Abstract: Bovine respiratory disease (BRD) is a complex disease that is associated with infection by bacterial and viral pathogens when cattle fail to adequately respond to stress. The objective of this study was to use gene set enrichment analysis of SNP data (GSEA-SNP) and a network analysis (ingenuity pathway analysis) to identify gene sets, genes within gene sets (leading-edge genes) and upstream regulators associated with BRD in pre-weaned dairy calves and beef feedlot cattle. BRD cases and controls were diagnosed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 67 publications
6
31
0
1
Order By: Relevance
“…Due to the relatedness of mycobacterial pathogens such as MAP, Mycobacterium tuberculosis and Mycobacterium bovis, loci that provide less genetic susceptibility to one pathogen might afford some protection to the other organism. In fact, loci on BTA3 where we identified association for pTB susceptibility in the current study, overlapped with loci previously reported in the literature that were associated with bovine tuberculosis susceptibility [28] and bovine respiratory disease susceptibility [29].…”
Section: Discussionsupporting
confidence: 85%
“…Due to the relatedness of mycobacterial pathogens such as MAP, Mycobacterium tuberculosis and Mycobacterium bovis, loci that provide less genetic susceptibility to one pathogen might afford some protection to the other organism. In fact, loci on BTA3 where we identified association for pTB susceptibility in the current study, overlapped with loci previously reported in the literature that were associated with bovine tuberculosis susceptibility [28] and bovine respiratory disease susceptibility [29].…”
Section: Discussionsupporting
confidence: 85%
“…In the same study, TNF was identified as the most significant upstream regulator in beef cattle, influencing 64 downstream genes that were associated with the immune response. 79 Comparisons between the beef and dairy populations in this studied identified 6 BRD-associated SNPs that were shared between the groups, located in the genes ADIPOQ, HTR2A, MIF, PDE6G, PRDX3, and SNCA. 79 All 6 genes are known to be involved in down-regulating TNF production and in the metabolism of reactive oxygen species.…”
Section: Genetics Of Disease Resistancementioning
confidence: 91%
“…79 Comparisons between the beef and dairy populations in this studied identified 6 BRD-associated SNPs that were shared between the groups, located in the genes ADIPOQ, HTR2A, MIF, PDE6G, PRDX3, and SNCA. 79 All 6 genes are known to be involved in down-regulating TNF production and in the metabolism of reactive oxygen species. 79 It is expected that the next decade will bring continued advancements in understanding of the genetic components of this pervasive syndrome.…”
Section: Genetics Of Disease Resistancementioning
confidence: 91%
See 1 more Smart Citation
“…being a member of a specific pathway) which are identified by significant (with comfortable threshold) SNPs of GWAS, is tested for over-representation in a specific pathway [9]. Recently a growing interest in gene set enrichment analysis has been observed in dairy cattle [8,10,11]. However, there are no published reports of gene set analysis of sheep GWAS dataset.…”
Section: Introductionmentioning
confidence: 99%